Water communities - Shaw, Rajib; Thaitakoo, Danai (Emerald, 2010)
Water is the key to human civilization. Most of the ancient civilization had its roots to river basins, where people-water interaction was the key aspect. Due to innovations of knowledge and technology and modernization of lifestyles, the human-water direct contact has become less significant. People have become more dependent to the system, and consequently, the closeness to water is gradually diminishing. It is however, a challenge on how to learn from the basic principles of water human interaction and apply those lessons to the current context of urban and rural settings. This book will provide a few analytical case studies on different aspects of water communities, which is defined as the human-water interaction process.
Keywords: Water and civilization.; elektronické knihy; electronic books